Analisa Faktor-Faktor Yang Mempengaruhi Kepuasan Pengguna E Study Dengan Human Organisation Technology (Hot-Fit) Model - Saputra, Septiyan Tri; Lusiana, Dewi; Oktavianto, Hardian (JSAI (Journal Scientific and Applied Informatics), 2024)
The purpose of this research is to determine the success rate of the Application E Study with the Human, Organization, Technology Evaluation Framework. (HOT-FIT Model). E Study application used to handle academic data and deliver academic information. Problem formulation How does service quality affect user satisfaction and the influence of user satisfaction and organization on net benefit. The results of the study are that Quality of Service (KL) has a significant influence on User Satisfaction (KP) with coefficients of 0.889 and C.R. 6,900. User satisfaction (CP) has a significant impact on Net Benefit (NB) with a coefficent value of 0.467 and a C.R value of 2.483. The results of the research show that the use of the E Study Application is successful because the user is satisfied with the features of the Application available on the E Study. The user is happy with the fast and responsiveservice